SCORE-IT: the Spot Sign score in restricting ICH growth─an Atach-II ancillary study - Goldstein, JN (Zeenat Qureshi Stroke Research Center, 2012)
INTRODUCTION: The ATACH-II trial is designed to evaluate whether intensive blood pressure reduction can reduce hematoma growth and improve outcome. However, it is difficult to determine, at presentation, which patients are at highest risk of ongoing bleeding, and will receive the most clinical benefit from blood pressure therapy. It may be that improved predictive markers will lead to efficient, personalized selection of optimal therapy. We hypothesize that specific imaging findings on CT angiography (CTA) and MRI will mark those patients who receive the most benefit from intensive blood pressure reduction. METHODS: Many patients enrolled in ATACH-II will undergo CTA and/or MRI as part of routine clinical care. We will perform a blinded analysis of these images. For CTA, we will determine the presence of contrast pooling (also termed contrast extravasation or the “Spot Sign”). In addition, we will calculate a Spot Sign Score, a score that includes number of Spot Signs, diameter, and contrast density. For MRI, we will focus on the presence, number, and location of cerebral microbleeds (CMBs) on sensitive T2*-weighted MRI sequences. RESULTS: We will test the hypothesis that patients with a Spot Sign will receive clinical benefit from intensive blood pressure reduction. In addition, we will determine whether patients with the highest Spot Sign Scores receive the most benefit from intensive blood pressure reduction. Finally, we will determine whether the absence of CMBs marks those at higher risk for hematoma expansion, and therefore more likely to benefit from treatment. CONCLUSION: This ancillary study offers the tremendous opportunity to determine whether imaging findings can risk stratify ICH patients for acute therapies aimed at limiting hematoma growth.